RATIONALITY IN THE SOCIAL SCIENCES: EVOLUTION IN SOCIAL INSTITUTIONS AND DECISION-MAKING - Komiljon Raxmatov (Modern American Journals, 2026)
This article examines the concept of rationality in the social sciences through the lens of its historical and theoretical evolution, with particular attention to decision-making processes within social institutions. The study analyzes how classical models of instrumental rationality have gradually expanded to include bounded rationality, institutional rationality, and context-dependent approaches shaped by cultural, normative, and structural factors. Special emphasis is placed on the role of social institutions as mediators that both constrain and enable individual and collective decision-making. Drawing on interdisciplinary perspectives from sociology, economics, political science, and philosophy, the article demonstrates that rationality is not a fixed or universal principle, but a dynamic and evolving construct influenced by institutional change and social complexity. The findings contribute to a deeper understanding of how rational decision-making adapts to modern societal challenges and provide a conceptual framework for further empirical research in social theory.
Keywords: Rationality, social sciences, decision-making, social institutions, bounded rationality, institutional change, social evolution.